Preliminary performance analysis using the PPP-RTK service of the National Land and Mapping Center in Taiwan - J.-Y. Lin; C.-H. Chu; F.-Y. Chu; K.-W. Chiang; M.-L. Tsai (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Low-cost navigation and positioning systems have become a prominent research field in recent years. In the autonomous vehicle domain, real-time accurate vehicle position determination within lanes is essential for high-level autonomous driving. Regarding real-time performance, while (Precise Point Positioning-Real Time Kinematic)PPP-RTK's corresponding accuracy is not as high as Network-RTK (NRTK), PPP-RTK can provide rapid positioning solutions with a single antenna and single Global Navigation Satellite System(GNSS) receiver. It also features lower bandwidth requirements and unidirectional transmission capabilities than NRTK, allowing more simultaneous users. This makes it a reliable choice when server-side hardware, software, and bandwidth resources are limited. In open-sky environments, autonomous vehicles often rely on GNSS for positioning. However, GNSS signals in urban canyons are susceptible to multi-path effects and NLOS (Non-Line-of-Sight) issues, leading to decreased positioning accuracy. Sensor fusion is the most common solution for maintaining real-time, robust, and high-precision navigation quality across various environments. This research proposes an integration of PPP-RTK and Inertial Navigation System (INS) framework to construct a real-time robust navigation system by integrating PPP-RTK and IMU data using an Extended Kalman Filter (EKF). The experimental equipment includes a tactical-grade Inertial Measurement Unit (IMU) and a low-cost receiver capable of receiving National Land Surveying and Mapping Center (NLSC) correction signals for PPP-RTK functionality. Furthermore, testing was conducted in various challenging outdoor urban environments to validate the proposed algorithm. A high-precision navigation-grade system was used as the reference solution to analyze the accuracy of the proposed real-time navigation system.Additionally, a NovAtel Pwrpak7D-E2 with its internal NovAtel OEM7 receiver utilizing TerraStar service for PPP-RTK implementation was used as a benchmark system to compare the gap between Taiwan's preliminary NLSC PPP-RTK development and existing products. A comparison with NLSC traditional RTK and INS integrated system was also provided.Results show that in GNSS open areas, the 2D Root Mean Square Error (RMSE) between the NLSC PPP-RTK system and EGI-M370 was 2.912 meters lower in accuracy than the benchmark system's 0.585 meters. Although the accuracy of the NLSC PPP-RTK service currently falls below TerraStar's, the system is still in its early development stages. With system parameter adjustment and optimization, it is expected to achieve accuracy comparable to TerraStar, providing a more competitive solution for low-cost autonomous navigation.